Government Authority in Regulating Employment Relations between Employers and Workers/Laborers in Indonesia - Rika Jamin Marbun; Abdurrahman Harits Ketaren; Siti Nurhayati (CV. AFDIFAL MAJU BERKAH, 2022)
The working relationship between employers and workers/labourers is civil/private in nature because it was born after the existence of a work agreement. The existence of jobs, orders and wages as elements of work relations is left to the parties. The work agreement as the basis of the employment relationship is an autonomous rule for employers and workers/laborers in exercising their rights and obligations. However, work agreements do not fully contain private elements. The position of the worker/laborer and the entrepreneur is not balanced, for example in terms of